(3GdeKd GdSGFQ aj COH GdcGJH hGdTGYQs - (3GdeHGQc Hf eMeO Hf eMeO Hf eMeO Hf nYrHO GdncpQje GdTjHGfqj GdLRQj, CHh GdSYGOGJ, eLO GdOjf, GHf GdCKjQ,J (B606 (3g` s
(3ChdgG (B:s
(3CSCd Gddg Cf jHdZfG ef GdMeO eG gh Cgdg hCf jYdefG ef GdHjGf s
(3BNQgG (B:s
(3Ydi Cfg djS ai dZJge CaUM efg hgPG EdG hLO ai GddZI GdYQHjI Ydi ESJGYgG Je GdLRA GdKGfi ef cJGH GdeKd GdSGFQ HMeO Gddg JYGdi s
(3fbdgG GdfGSN ef fSNI HNW hdO GdeUfas
(3Ydi GdfSNI Gdefbhd efgG SeGY GdcJGH hbQGAJg Ydi GdeUfa hNW GddeUfa HJUMjM Pdc SfI (B631 (3g`s
(3GNJdaJ GdeSWQI ai GdChQGb GdCNjQI aUGQJ (B36 (3SWQ ai GdUaMIs
(3cJHJ GdUaMI GdChdi HNW eZQHi eMOK s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
Keywords: (3GdHdGZIs